DESIGN AND DEVELOPMENT OF PHOTOVOLTAIC INTEGRATED GRID-TIED ACTIVE POWER FILTER WITH FUZZY LOGIC CONTROLLERS FOR MAXIMUM POWER POINT TRACKING AND DIRECT CURRENT LINK VOLTAGE REGULATION - Zhanbolatov, Arshyn (Nazarbayev University School of Engineering and Digital Sciences, 2025)
With growing carbon emissions, energy demand and share of nonlinear loads, photovoltaic (PV) integrated active power filter (APF) systems are being widely adopted in the power sector as they provide dual benefits of supplying PV generation and enhancing the grid power quality (PQ). Maximum power point tracking (MPPT) and direct current (DC) link voltage regulation control techniques are needed in these systems to maintain maximum PV and APF efficiencies under changing environmental and loading conditions. Performances of conventional perturb and observe (P&O) and proportional-integral (PI) techniques degrade significantly in case of large and rapid fluctuations in the operating conditions making them less suitable for highly dynamic systems. In this MSc thesis, PV integrated grid-tied shunt APF with fuzzy logic controllers (FLCs) for MPPT and DC link voltage regulation are designed and developed to improve the efficiency of the PV system and reduce total harmonic distortions (THDs) of the grid currents under large and rapidly varying environmental and loading scenarios. Type-1 Mamdani fuzzy inference systems with simple 5x5 and 7x7 rule bases and set of trapezoidal and triangular membership functions are used for the FLCs’ design. Simulation studies and experimental test were conducted in MATLAB/Simulink and laboratory setup to evaluate and validate the performance of the proposed system and compare it against the system with the P&O and PI controllers. The simulation results show that the proposed FLCs provide more accurate and faster responses compared to the conventional controllers under step changes in the solar irradiance and loading resulting in higher PV efficiency and harmonic compensation capability. The experimental test confirmed that the PV integrated APF was able to supply PV active power to the load and achieve grid current THD from 26.99 % to 4.19 % which is within the 5 % limit specified by the Institute of Electrical and Electronics Engineers (IEEE) 519 standard.
Keywords: type of access: open access; Maximum Power Point Tracking (MPPT); Active Power Filter (APF); Fuzzy Logic Controller (FLC)